Alternative Life-History in Native Trout (Salmo spp.) Suppresses the Invasive Effect of Alien Trout Strains Introduced Into Streams in the Western Part of the Balkans - Škraba Jurlina, Dubravka; Marić, Ana; Mrdak, Danilo; Kanjuh, Tamara; Špelić, Ivan; Nikolić, Vera; Piria, Marina; Simonović, Predrag (Frontiers in Ecology and Evolution, 2020)
Diversity of native trout fish Salmo spp. comprises a variety of nominal taxa in Serbia, Montenegro and Bosnia and Herzegovina. Recent mapping of the resident trout detected brown trout S. trutta (sensu stricto) of the Atlantic (AT) mtDNA lineage introduced into populations of both tentative Danubian trout S. labrax and of tentative Adriatic trout S. farioides belonging to the Danubian (DA) and Adriatic (AD) mtDNA lineages, respectively. In addition, an introduction of the tentative Macedonian trout S. macedonicus of the AD lineage was detected in the one native population of the tentative S. labrax. In almost all recipient non-migratory trout populations, a cross breeding between the native and introduced trout was detected by heterozygosity in either only LDH-C nuclear locus, or in LDH-C and particular microsatellites’ loci. Exception is one population where both resident and migratory, lake-dwelling individuals of the tentative Adriatic trout spawned at the downstream section of a stream in Montenegro, none of microsatellites’ alleles of Atlantic brown trout that were introduced into the upstream section was detected. The occurrence of cross breeding between Adriatic and brown trout was evident in the upstream, isolated section. It seems that migrating, lake-dwelling Adriatic trout in combination with their resident, stream-dwelling conspecifics suppress introgression of genes from those situated upstream, strongly introgressed by brown trout. Having this in sight, it is noteworthy to warn on the occurrence of the migratory brown trout in the Danube River at the broader Iron Gate Gorge area. They were recorded to migrate in late summer and early fall from the Iron Gate One reservoir to the lower sections of tributaries devoid of any trout fish. However, some of those streams home very special native trout of the DA lineage in their short-extending upper sections. Those native trout populations are so far still out of contact with the reservoir-dwelling trout. However, having in mind the resilience of trout featuring the migratory life-history, the outcome of this introduction could be deleterious for those natives very precious in conservational sense.